The impact of code smells on software bugs: a systematic literature review - Cairo, Aloisio S. (2018)
A.S.C. and G.d.F.C. together searched for eligible papers from the publication databases and read the eligible papers carefully. A.S.C., G.d.F.C., and M.P.M. wrote the article. All authors read and approved the final manuscript.